(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction : Lip prints are an adjuvant tool for identification in forensic medicine. The grooves on the lips have discrete characteristics to make it different from one other. This study was conducted on 24 pairs of twins out of which 22 pairs were Monozygotic twins and 2 pairs were Dizygotic twins. Dizygotic twins are unique in all aspects while Monozygotic twins are similar phenotypically and genotypically. The objective of this study is to find the most common pattern in the twins , the commonest pattern among the male and female twins and to know the variations in the pattern of lip prints among Monozygotic and Dizygotic twins. Materials and Methods: A lipstick, drawing chart and magnifying lens were the materials used to record the imprints of the lips. A four compartment method with a clockwise direction approach was used and the analysis was done based on Suzuki and Tsuchihashi classification. Results: The present study shows Type 1’ was the most common lip prints observed among the 24 pairs of twins. This pattern was predominantly present in the right lower lip quadrant. Out of the study subjects of 24 pairs of twins, 38 were males and 10 were females in which Type I ‘ is common in males and type I is common in females. Among the monozygotic twins those which had < 50 % resemblance were 14 pairs, 50% resemblance were 6 pairs, >50% resemblance were 2 pairs in which Type is the commonest. Among the dizygotic twins, both the pairs were totally different from each other yet Type was the common pattern. Conclusion: Based on the analysis of the lip print patterns among monozygotic twins, though similarities were prevailing between them , they are not identical .Whereas among dizygotic twins both the pairs of twins are unique. Hence Lip print can be utilized as a differentiating tool for identification.